Bioethanol Production from Iles-Iles and Sorghum Starch as Raw Materials (Effect of CaCl 2 Addition and Saccharification Time) - Kusmiyati, Kusmiyati; Mahmudi, Ali (UI Scholars Hub, 2014)
Bioethanol produced from agricultural sources is one alternative energy that has been developed to substitute for petroleum. However, the use of food sources such as corn and cassava to produce bioethanol still face obstacles that lead to the scarcity of food and an increase in food prices. The aim of this study was to produce bioethanol from sorghum and iles-iles, which are not used by humans as food, especially in Indonesia. For both materials, the variables studied were saccharification time (4, 8, 24, and 48 h) and concentration of CaCl2 added to the liquefaction slurry (0, 100, 200, 300, and 400 mg/L). The bioethanol was produced by enzymatic hydrolysis, which consists of liquefaction usinga-amylase at 1.6% v/w (t = 1 h; T = 95-100 °C; pH 6) and saccharification of the liquefaction slurry by using b- amylase at 3.2% v/w (t = various; T = 60 °C; pH 5) and fermentation by Saccharomyces cerevisiae (t = 120 hours; pH 4, 5; yeast 5g). The best conditions were obtained for sorghum at saccharification t = 24 h, which resulted in the highest ethanol yield, 91.5 g/L, and for iles-iles at t = 48 h, which yielded 107.1 g/L. The optimum amount of CaCl2 to be added was 200mg/L, which resulted in the highest ethanol yield, 98.5 g/L and 92.4 g/L for sorghum and iles-iles, respectively. This results shows that sorghum and iles-iles are promising raw materials for the production of bioethanol, since they produce it in large amounts.